2022
DOI: 10.1002/bimj.202200104
|View full text |Cite
|
Sign up to set email alerts
|

Against the “one method fits all data sets” philosophy for comparison studies in methodological research

Abstract: Many methodological comparison studies aim at identifying a single or a few "best performing" methods over a certain range of data sets. In this paper we take a different viewpoint by asking whether the research question of identifying the best performing method is what we should be striving for in the first place. We will argue that this research question implies assumptions which we do not consider warranted in methodological research, that a different research question would be more informative, and how thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Conditional answers imply that concepts such as global optimality are to be replaced by more shaded counterparts. If, for a given criterion, the nature of the optimal method further differs across data types, one ends up in a "one size does not fit al" type of scenario (Strobl & Leisch, 2022), which calls for a reporting in terms of proper conditional statements. A formally very similar scenario is well known in clinical trial research and occurs if there is no therapeutic alternative that outperforms all other alternatives for all (types of) patients; this further calls for a precision medicine approach.…”
Section: Possible Answers Resulting From Benchmarking Studiesmentioning
confidence: 99%
“…Conditional answers imply that concepts such as global optimality are to be replaced by more shaded counterparts. If, for a given criterion, the nature of the optimal method further differs across data types, one ends up in a "one size does not fit al" type of scenario (Strobl & Leisch, 2022), which calls for a reporting in terms of proper conditional statements. A formally very similar scenario is well known in clinical trial research and occurs if there is no therapeutic alternative that outperforms all other alternatives for all (types of) patients; this further calls for a precision medicine approach.…”
Section: Possible Answers Resulting From Benchmarking Studiesmentioning
confidence: 99%
“…The second data task we consider in our experiment is differential gene expression analysis, which aims at identifying genes that show differences in their expression levels between two or more conditions (Soneson & Delorenzi, 2013). Of the many methods that have been proposed for this task (Seyednasrollah et al, 2013), the more recent ones usually expect RNA-Seq data as input, which means that gene expression is measured as nonnegative counts (Rigaill et al, 2018).…”
Section: Data Analysis Task Ii: Differential Gene Expression Analysismentioning
confidence: 99%
“…Therefore, we published a simulation study protocol, which includes details on the simulation setup, sample size, data-generating mechanism, and outcomes (https://osf.io/5wmg9). Our simulation study was designed, as suggested by Strobl et al [30], to have the complexity of real data and to reflect scenarios that are realistic but not idealistic [30]. This can be considered a strength of our study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%